The metabolic syndrome, thiazolidinediones, and implications for intersection of chronic and inflammatory disease - Jerry R. Colca; Philipp E. Scherer (Elsevier, 2022)
Background: Chronic disease appears connected to obesity. However, evidence suggests that chronic metabolic diseases are more specifically related to adipose dysfunction rather than to body weight itself. Scope of review: Further study of the first generation "insulin sensitizer" pioglitazone and molecules based on its structure suggests that is possible to decouple body weight from the metabolic dysfunction that drives adverse outcomes. The growing understanding of the mechanism of action of these agents together with advances in the pathophysiology of chronic metabolic disease offers a new approach to treat chronic conditions, such as type 2 diabetes, fatty liver disease, and their common organ and vascular sequelae. Major conclusions: We hypothesize that treating adipocyte dysfunction with new insulin sensitizers might significantly impact the interface of infectious disease and chronic metabolic disease.